La ricerca universitaria per l’innovazione applicata al territorio: SI2G, spin off universitario - Zingaretti, Primo; Malinverni, Eva Savina (GEOmedia, 2009)
SI2G, university spin-off SI2G is a spin-off company of Polytechnic University of Marche, built up in 2008 by a cross-curricular team belonging to the Engineer faculty. SI2G goes into business as ICT service and solution provider ranging from Remote Sensing and landscape monitoring (in particular Land Cover/Land Use mapping) to up-to-date computer cartography, Web-GIS solutions and Geographic Information Systems.